2023
DOI: 10.1037/cdp0000397
|View full text |Cite
|
Sign up to set email alerts
|

“You don’t believe in God? You ain’t Black”: Identifying as atheist elicits identity denial from Black ingroup members.

Abstract: Objective: Anecdotal narratives and recent qualitative research with Black atheists document experiences of racial identity denial from the target's perspective. However, no research to date has examined whether Black perceivers perceive Black atheists as being weakly identified with their race. Because belief in God is often inextricably linked with Black racial identity in the Black community, we hypothesized that Black atheists would be perceived as less Black than nonatheists. Method: Black/African America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…We also did not find any evidence that White individuals perceive Black individuals who identify as atheist as any less racially identified than Black individuals who identify as Christian or whose religious affiliation is not known. Although recent research has demonstrated that Black individuals challenge the racial identity of Black atheists in the United States, this may be an exclusively intraracial phenomenon (Abbott et al, 2020; Howard et al, 2021; Swann, 2020). It is important to note that the present study used perceived Black identity of a Black target as a dependent variable given this was the most appropriate for a U.S. context.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We also did not find any evidence that White individuals perceive Black individuals who identify as atheist as any less racially identified than Black individuals who identify as Christian or whose religious affiliation is not known. Although recent research has demonstrated that Black individuals challenge the racial identity of Black atheists in the United States, this may be an exclusively intraracial phenomenon (Abbott et al, 2020; Howard et al, 2021; Swann, 2020). It is important to note that the present study used perceived Black identity of a Black target as a dependent variable given this was the most appropriate for a U.S. context.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that these individuals experience different types of biases than their single stigmatised counterparts and these biases may be currently overlooked in the literature. For example, recent research suggests that the intersection of an atheist identity with race leads to unique experiences of bias among communities of colour in the United States (e.g., racial identity denial; Abbott et al, 2020; Howard et al, 2021). There needs to be more cross‐cultural research examining the intersection of race and religion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations